2007
DOI: 10.1080/09273940701244509
|View full text |Cite
|
Sign up to set email alerts
|

Course of Macular Edema in Uveitis under Medical Treatment

Abstract: This study demonstrates the overall favorable visual prognosis of uveitic macular edema under medical treatment. The presence of an epiretinal membrane is an important factor associated with medical treatment failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 29 publications
6
33
1
5
Order By: Relevance
“…Disturbed IS/OS line integrity is associated with low VA. Ota et al reported that patients with a disturbed IS/OS line had poorer VA than those with an intact IS/OS line in the central and branch retinal vein occlusion (RVO) (8,9) . Shin et al found lower VA in diabetic retinopathy and in RVO patients with disturbed IS/OS lines (10,11) . Erdem et al showed that 65% of the active uveitis patients had interrupted IS/OS lines, but 30.8% of the patients regained the integrity of the IS/OS line during remission (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbed IS/OS line integrity is associated with low VA. Ota et al reported that patients with a disturbed IS/OS line had poorer VA than those with an intact IS/OS line in the central and branch retinal vein occlusion (RVO) (8,9) . Shin et al found lower VA in diabetic retinopathy and in RVO patients with disturbed IS/OS lines (10,11) . Erdem et al showed that 65% of the active uveitis patients had interrupted IS/OS lines, but 30.8% of the patients regained the integrity of the IS/OS line during remission (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Murakami et al reported that in diabetic macular edema patients, the areas under the cystoid spaces had increased transverse length of disrupted or faint IS/OS lines and disrupted ELM lines than those without cystoid spaces (11) . OB patients also suffer from recurrent macular edema attacks due to recurrent uveitis, which may lead to photoreceptor damage.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography has also been used to diagnose, assess, and monitor the therapeutic response in uveitic macular edema [48,51,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. In a recent study, Sugar et al [86] tried to identify a clinically meaningful threshold for change in uveitic macular edema evaluated by OCT. A 20 % change in retinal thickness in patients with uveitic macular edema was found to be optimal for clinically important changes in visual acuity.…”
Section: Use Of Optical Coherence Tomography Technology In Uveitis Prmentioning
confidence: 99%
“…Estudos têm demonstrado que o uso de drogas imunossupressoras, como ciclosporina e azatioprina, em combinação com esteróides sistêmicos, permitem o controle da inflamação intraocular com uma dose menor de esteróide, com consequente redução dos efeitos gerais que acompanham os esteróides de uso sistêmico (7) . A tomografia de coerência óptica (OCT), apesar de descrita há mais de dez anos, tem emergido como uma nova técnica que, através de imagens de alta resolução de cortes seccionais da retina, pode auxiliar no diagnóstico, na monitorização e na análise quantitativa de doenças que acometem a mácula e a cabeça do nervo óptico (8)(9)(10) . No caso descrito anteriormente, realizamos a OCT precocemente, evidenciando edema e descolamento seroso da retina.…”
Section: Discussionunclassified
“…No caso descrito anteriormente, realizamos a OCT precocemente, evidenciando edema e descolamento seroso da retina. Após 35 dias de tratamento, pudemos acompanhar a resolução do quadro através de nova OCT, corroborando dados sugestivos de prognóstico favorável dos casos de oftalmia simpática submetidos a tratamento médico precoce (10) . Dessa forma, oftalmologistas devem estar cientes da variedade de características morfológicas das diferentes formas de uveítes que podem ser observadas com o uso da OCT. Esse reconhecimento pode auxiliar no diagnóstico precoce, que deve ser sempre precedido de uma boa anamnese, exame de fundo de olho com o oftalmoscópio binocular indireto e a angiofluoresceinografia (9) .…”
Section: Discussionunclassified